Maternal Care and Control as Mediators in the Relationship Between Mothers' and Adult Children's Psychosocial Problems. Issue 3 (2nd July 2016) - Arroyo, Analisa; Segrin, Chris; Curran, Timothy M.
ABSTRACT: The current research investigated the relationship between mothers' and adult children's psychosocial problems through two different aspects of maternal interactions. Data were collected from family triads ( N = 286), including a mother, a child, and a sibling. Mothers and their adult children completed measures of depression, loneliness, and self-esteem. The assessment of the maternal interaction variables (i.e., maternal care and maternal control) involved the perspectives of a sibling to minimize common method variance. Results partially supported the hypothesized model, wherein maternal care (but not maternal control) mediated the relationship between mothers' depression, loneliness, and self-esteem to that of their children. Specifically, mothers who reported higher levels of psychosocial problems had children who reported that their mothers were less caring and, in turn, less maternal care was associated with higher levels of psychosocial problems in their young adult children.